2007
DOI: 10.1521/aeap.2007.19.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Current Sexual Activity and Risky Sexual Behavior in Older Men With or At Risk for HIV Infection

Abstract: In a cross-sectional analysis, we investigated frequency of sexual activity and factors associated with risky sexual behavior among 624 older men, aged 49−80, with or at risk for HIV infection. During the prior 6 months, 75% reported sexual activity with at least one partner, and one quarter of both the HIV-negative and HIV-positive men had more than one sexual partner. Only 18% of the HIVnegative men and 58% of the HIV-positive men always used condoms with their sexual partners. Factors independently and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 38 publications
7
57
1
2
Order By: Relevance
“…Entretanto, o advento dos medicamentos que melhoram o desempenho sexual e possibilitam o estabelecimento de novas e múltiplas parcerias sexuais, e a disponibilidade da terapia antiretroviral altamente ativa (HAART) anteriormente não existente, têm favorecido a infecção pelo HIV de pessoas com mais idade, porém, com possibilidade de sobrevida maior quando tratadas adequadamente 10 .…”
Section: Introductionunclassified
“…Entretanto, o advento dos medicamentos que melhoram o desempenho sexual e possibilitam o estabelecimento de novas e múltiplas parcerias sexuais, e a disponibilidade da terapia antiretroviral altamente ativa (HAART) anteriormente não existente, têm favorecido a infecção pelo HIV de pessoas com mais idade, porém, com possibilidade de sobrevida maior quando tratadas adequadamente 10 .…”
Section: Introductionunclassified
“…Most research examining sexual risk behaviors in older adults has focused on HIV-seronegative persons (e.g., Abel and Werner 2003;Allison-Ottey et al 1999;Kwiatkowski and Booth 2003;Maes and Louis 2003;Winningham et al 2004); only a few studies have characterized sexual behavior in older adults already living with HIV/AIDS (e.g., Cooperman et al 2007;Schable et al 1996;Siegel et al 2004). Schable et al (1996) examined sexual behavior in 59 HIV-infected women who were 50 years of age or older at the time of their AIDS diagnosis and found that 55% had no sexual partners in the past year, 36% had one partner, and 9% had more than one partner.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most plausible reasons for the varying conclusions is that the focus of our study is on men who received EDD as part of clinical practice, whereas nearly all of the previous reports linking EDD to risky sexual behavior were conducted in non-clinical samples in high risk groups, including MSM [4][5][6][7][8][9][10][11][12]16,25 , substance abusers 11,26 , and HIV-infected men outside of clinical settings. [13][14][15] In nearly all of these studies, the association of EDD and risky sexual behavior was consistently the strongest in men who also used stimulant drugs such as methamphetamines, ecstasy, or gamma-hydroxybutyrate (GHB), which were rare in our study sample. The source of EDD may also influence its relationship with risky sexual behavior.…”
Section: Discussionmentioning
confidence: 72%
“…3 EDDs have also been linked to high-risk sexual behavior in some groups of men at increased risk for HIV transmission, in particular men who have sex with men (MSM), men who use recreational or illicit drugs, and HIV-infected men. [4][5][6][7][8][9][10][11][12][13][14][15][16] Because of their association with risky behavior, some have argued that EDD medications should be classified as controlled substances.…”
Section: Introductionmentioning
confidence: 99%